RANCANGAN WIRELESS INTRUSION DETECTION SYSTEM MENGGUNAKAN SNORT - Irwan Agus Sobari (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2015)
Implementation of wireless networks do not have a mature information security plan will open up a lot of vulnerabilities that will be exploited by intruders or people who are not responsible. The development of wireless networks is rapidly increasing making it vulnerable to a number of security threats. Some attack that occur are spoofing, denial of service, backdoor, man in the middle attack and the others. This is due to the wireless network can not be limited to a building and wireless network transmission of data packets is very easy to catch people who are not responsible. It is Therefore necessary to build a good system and not expensive but very useful for the company. Systems built the intrusion detection system using SNORT that has the function to monitor wireless network traffic, looking for a data packet or suspicious behavior patterns to be recorded into a log and warning to notify the network administrator. This research is expected to help network administrators to monitor and learn some new types of attacks that occur and protect computer network that exist today.